2020
DOI: 10.3390/cells9071586
|View full text |Cite
|
Sign up to set email alerts
|

Role of FOXO Transcription Factors in Cancer Metabolism and Angiogenesis

Abstract: Forkhead box O transcription factors (FOXOs) regulate several signaling pathways and play crucial roles in health and disease. FOXOs are key regulators of the expression of genes involved in multiple cellular processes and their deregulation has been implicated in cancer. FOXOs are generally considered tumor suppressors and evidence also suggests that they may have a role in the regulation of cancer metabolism and angiogenesis. In order to continue growing and proliferating, tumor cells have to reprogram their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 157 publications
0
25
0
Order By: Relevance
“…Previous studies indicated that FOXO transcriptional activity is regulated by phosphorylation modification and that the serine/threonine kinase AKT regulates the activity of Forkhead transcription factors by phosphorylating them and inhibiting their unclear translocation [ 9 , 37 ]. To investigate whether the increase of FOXO in the nucleus after pathogenic bacteria infection is affected by AKT, we first detected the content of FOXO in the cytoplasm and nucleus by western blotting after knockdown of Akt of shrimp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that FOXO transcriptional activity is regulated by phosphorylation modification and that the serine/threonine kinase AKT regulates the activity of Forkhead transcription factors by phosphorylating them and inhibiting their unclear translocation [ 9 , 37 ]. To investigate whether the increase of FOXO in the nucleus after pathogenic bacteria infection is affected by AKT, we first detected the content of FOXO in the cytoplasm and nucleus by western blotting after knockdown of Akt of shrimp.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the phosphorylation of FOXO transcription factors by AKT causes their degradation in the cytoplasm and enhances cell survival by blocking the transcription of death receptor ligands TRAIL and Fas, and of pro-apoptotic Bcl-2 members Bim and BNIP3 [112]. The implication of FOXOs in the development of MDR is highlighted by their key role in regulating drug efflux pump ABCD1 in leukemic and breast cancers and by eliciting resistance to agents that act via the accumulation of ROS [113]. A deeper understanding of the role of FOXOs in these two processes will enable the development of effective therapeutics.…”
Section: Pi 3 K/akt Pathway In Multi-drug Resistancementioning
confidence: 99%
“…Akt-mediated phosphorylation inactivates FoxO proteins, thereby inhibiting apoptotic and antiproliferative transcriptional programs, and thus linking diabetes and cancer [ 97 ]. It is thought that FoxO attenuates the Warburg effect and glucose uptake at least partly by antagonizing c-Myc by several mechanisms: by directly binding the promotor regions of c-Myc responsive genes, by augmenting the transcriptional repressors of the MAD/MXD family, and by facilitating the expression of microRNAs that target c-Myc [ 98 , 99 , 100 ]. Some of FoxO-mediated effects on metabolism are summarized in Table 1 .…”
Section: Molecular Drivers Of Metabolic Changes In Cancer Cellsmentioning
confidence: 99%
“…Despite the fact that both enzymes, Glutaminases 1 and 2 (GLS1 and GLS2), are able to assimilate glutamine (convert it to glutamate and ammonia), apparently their levels and functions upon EMT are regulated differently. GLS1 was shown to be induced by TGF-beta and is essential for EMT in lung cancer cells, hepatocellular carcinoma [ 100 ], and breast cancer [ 101 ]. At the same time, expression of GLS2 was [ 170 ] inversely associated with EMT and decreased cancer stem-cell properties [ 171 ].…”
Section: Epithelial–mesenchymal Transition (Emt) and Associated Mementioning
confidence: 99%